Mechanical properties of nanoporous metallic glasses: Insights from large-scale atomic simulations. (April 2020) - Lin, Wei-Hui; Teng, Yun; Sha, Zhen-Dong; Yuan, Su-Yue; Branicio, Paulo Sergio
Abstract: While recent attention has been directed towards fabricating porous metallic glasses (MGs) with a wide range of pore sizes varying from nanometer to micrometer owing to their unique mechanical properties, there has been so far little or no atomic-level understanding of the deformation and failure mechanisms involved. Here we systematically investigate the mechanical response of nanoporous MGs under uniaxial tensile and compressive tests via large-scale molecular dynamics simulations. A scaling law is observed for the ultimate strength. Results show that nanoporous MGs fail by necking in tension. However, shear banding prevails when the ligaments possess a low slenderness ratio less than 2.0 and are inclined to the loading direction. Furthermore, the compressive strength value is found to be lower than that under tension due to the surface energy effect, which is contrary to the tension/compression asymmetry observed in monolithic MGs. Our study provides an atomic-level understanding of the fundamental failure mechanism in nanoporous MGs, which may offer new insights to the design and application of nanoporous MGs. Highlights: A scaling law is observed for peak strength in nanoporous metallic glasses. The failure mechanism depends on the ligament slenderness ratio and loading mode. The failure mode transits from necking to localized shear banding. A tension/compression asymmetry is revealed in nanoporous metallic glasses due to the surface energy effect.